THE NATURE’S POTENTIAL MULTIPURPOSE GIFT – PAPAYA (CARICA PAPAYA LINN.): A COMPLETE OVERVIEW - Bhadane, Vishal; Belemker, Sateesh; Mali, Bhupesh (Asian Journal of Pharmaceutical Research and Development, 2013)
Papaya (Carica papaya Linn.), an herbaceous fruit crop belonging to the family Caricaceae, has garnered popularity among researchers due to its nutritional and potent pharmacological value. It is often seen in orange-red, yellow-green and yellow-orange hues, with a rich orange pulp. The fruit is not just delicious and healthy, but whole plant parts, fruit, roots, bark, peel, seeds and pulp are also known to have medicinal properties. It is regarded as an excellent source of ascorbic acid, a good source of carotene, riboflavin and a fair source of iron, calcium, thiamin, niacin, pantothenic acid, vitamin B-6 and vitamin K. Several studies on different parts of carica papaya material used in extracting were highlighted. Extracts from different parts of Carica papaya plant have shown their positive effects when used as anti-microbial, anti-oxidant, antimalarial, anti-ulcer, anti-HIV, anti-inflammatory, anti-cancer, anti-hypertensive, anti-fertility, anti-fungal and anti-diabetic. In the present review nutritional value of the Carica papaya and wide pharmacological properties of its various parts in different extracts have been discussed to provide collective information on this multipurpose commercial fruit crop